Концепт ікони у творах українських письменників - Осадча, О. (Інститут народознавства НАН України, 2008)
Products of writers displayed the household sides of a rural life, belief in the God and love to the native ground. National icons have embodied universal and individual, that has defined originality Ukrainian national painting. The icon in family was means of education and preservation spiritual continuity of Ukrainian to people.